Insight into curdlan alleviating quality deterioration of frozen dough during storage: Fermentation properties, water state and gluten structure - Beibei Zhao; Liuyu Hou; Ting Liu; Xinru Liu; Shijian Fu; Hua Li (Food Chemistry: X, 2023)
Curdlan was effective in alleviating quality deterioration of frozen dough during storage. This research explored the mechanisms from perspectives of fermentation properties, water state and gluten structure of frozen dough during storage, and the performance of corresponding steamed bread. Results showed that curdlan addition improved the gas-releasing capability and gas-holding capability of frozen dough, meanwhile enhanced the specific volume and textural properties of corresponding steamed bread. The melting enthalpy and NMR results demonstrated that curdlan restricted the conversation of bound water into freezable water, and inhibited the moisture migration in frozen dough. Frozen dough with 0.5% curdlan had significantly lower gluten macropolymers (GMP) depolymerization degree and free sulfhydryl (SH) content than the control, indicating that curdlan alleviated the depolymerization of GMP. Microstructure results proved that the deterioration of the structure was retarded by curdlan. This study contributes to understanding the theories for curdlan alleviating the deterioration of frozen dough during storage.